The politics of waste picking: Reflections from the upscaling of a co-management model for recyclable waste in Buenos Aires (Argentina) - Carenzo, Sebastian (2021)
In Argentina, the organization of waste picker cooperatives has enabled these organizations to impose their approach and point of view in the system of waste management derived from the Integrated Solid Waste Management (ISWM) model. In this context, the experience of the cooperatives of the Autonomous City of Buenos Aires (CABA) stands out, as it paved the way for a co-management model that was unprecedented in the country. Since then, the "Buenos Aires System" has been promoted by the Argentine federation of waste pickers (FACCyR), as the model to be implemented throughout the country. The differences between the CABA and other jurisdictions raises significant questions regarding the adaptability of this model. Based on a Political Ecology of Waste, we address this question by analyzing the process of expansion of this model following the Jóvenes en Progreso cooperative in the municipality of Lomas de Zamora (Province of Buenos Aires).